(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the frequency of common bacterial isolates and antibiotic sensitivities in patients with community acquired bed sores. Study Design: Cross-sectional study Place and Duration of Study: Department of Medicine, DHQ Teaching Hospital, KDA Kohat from July 2018 to July 2019. Methodology: 220 patients were enrolled from both genders. Patient’s comprehensive histories and clinical review carried out and regular inquiries followed. Within 48 hours of admission / referral, bed sores were examined with a cotton swab from all patients. After the bacteria were found, susceptibility was tested to widely used antibiotics. Results: Male to female ratio was 2.55:1. Average age was 37.15±10.91. Escherichia Coli was found in majority of cases which were 57.27%. Conclusion: Culture and sensitivity were practiced in patients with bed sores acquired from the culture. This will not only allow patients to seek adequate care, but also deter the indiscriminate use of antibiotics and avoid further production of bacterial drug resistance.